PENERAPAN EXTREME PROGRAMMING PADA APLIKASI PELAPORAN AKTIVITAS DAKWAH DAI BENGKALIS - Muhammad Azmi; Elvi Rahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Dai is a person who is a social mobilization agent who helps the community in developing morals and becomes a liaison between the government and society to create a religious and harmonious life. The problems that occur in the process of reporting dai activities still use manual methods, take a lot of time, are less efficient, and are difficult to monitor in a timely manner. To solve this problem, an Android-based reporting system was created to assist dai in the reporting process. Extreme Programming was chosen as a system development method because this method is suitable for handling changing user needs. This system development uses the Laravel framework for the backend, Flutter for the frontend, and MySQL as the database. Testing is carried out using the black box testing method to ensure each feature, including reporting, user data management, and report monitoring, functions according to specifications. The research results show that the system developed is able to increase the efficiency and effectiveness of reporting on dai activities, replacing less practical manual methods. In addition, this application allows sub-district and village coordinators to compile reports in real-time, making it easier to monitor and evaluate programs.